Methanolic Stem Extract of Pereiria medica: Concentration-dependent DPPH and ABTS Radical Scavenging Activity (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Medicinal plants are an important reservoir of bioactive compounds that may offer safer and effective alternatives for managing free-radical damage. Pereiria medica Lindl. (Tree turmeric), widely used in the indigenous system of medicine was studied for its in vitro scavenging activity. Objective: To evaluate the in vitro free-radical scavenging activity of the methanol stem extract of P. medica using DPPH and ABTS assays. Methods: Stem material was extracted with methanol and tested at multiple concentrations for radical-scavenging activity by DPPH and ABTS spectrophotometric assays. Data were analyzed by linear regression to determine concentration–response relationships and IC50 values. Results: The methanol stem extract exhibited concentration-dependent radical scavenging in both assays. Calculated IC50 values were 57.10 μg/mL (DPPH) and 53.63 μg/mL (ABTS), indicating comparable potency across the two radical systems. Conclusion:The methanolic stem extract of P. medica demonstrated significant in vitro antioxidant activity, supporting its traditional use and warranting further phytochemical characterization and in vivo evaluation.
Keywords: Pereiria medica; methanol extract; antioxidant; DPPH; ABTS; IC50